Understanding genetic diversity and population structure of CIMMYT and IITA early maturing provitamin A maize (Zea mays L.) inbred lines using phenotypic traits and SNP markers for variable tolerance to drought and heat stress - Mudadirwa, Derek; Olakojo, Samuel Adelowo; Ndhlela, Thokozile; Mhike, Xavier; Shayanowako, Admire Isaac Tichafa (Springer Nature, 2025)
Understanding genetic relationships of maize inbred lines before integrating them into a breeding program is crucial for optimizing heterosis. In this study we assessed the genetic diversity and population structure of 188 early maturing provitamin A maize inbred lines sourced from CIMMYT and IITA using 3.3 K SNPs markers and phenotypic traits data. The results showed highly significant statistical variability (p < 0.000) for key phenotypic traits such as, anthesis date (AD), anthesis-silking interval (ASI), senescence (SEN), ears per plant (EPP) and grain yield (GYD). Inbred lines DS19753, TZMI1989, DS197-206 and DS197-338 had high grain yield under drought and heat stress conditions whilst CML 486, DS197-308, DS197-185, and DS197-318 performed better under non-drought and heat stress conditions. The genetic diversity analysis revealed moderate genetic diversity (GD) of 0.24, and a polymorphic information content (PIC) of 0.20. A minor allele frequency (MAF) of 18% suggested relatively low genetic variation amongst the inbred lines whilst observed heterozygosity (Ho) of 0.02 and Fixation Index (F) of 0.90 indicated fixation of most loci in the inbred lines. Delta K was highest at K = 2 suggesting presence of two distinct genetic sub-populations. Analysis of Molecular Variance indicated that the estimated variance amongst the two populations (0.001) was minimal whilst most of the genetic variance occurs within populations (0.499). The phenotypic diversity revealed supported by genotypic variations among the assessed genotypes suggests a possibility of successful selection of superior drought and heat tolerant provitamin A maize inbred lines that can be used for developing hybrids.